Between Challenge, Surrender, And Ruling Authority in Andalusian Poetry (Zien Journal of Social Sciences and Humanities, 2022)
We tried through this study to shed light on two positions adopted by pre-Islamic poetry about the environment that embraced it. We wanted to reveal the depths of the poet's psyche, its secrets, his ability to express, and the strength of his response to the surrounding influences, then give it an existential dimension.Hence, it was necessary for us to show the positions of the Andalusian poet towards the various aspects of life (conflicts), and we found him submissive, submissive at times and defiant, steadfast at other times. And for the sake of this study, we chose in Andalusian poetry “challenge and surrender on the one hand and the ruling authority on the other,” which the Andalusian poet took existential issues and fateful questions, which made him enter into a psychological struggle that he translated in different ways, through several symbols that expressed his declaration of surrender in front of some life obstacles, Then it soon explodes other symbols with which he faced and challenged most of the harsh conditions of life, as most poets oscillate between the positions of surrender and challenge. And from it, they expressed a true human experience, its content is existence and destiny. In wars and conflicts, its hero and knight is the warrior, defending his tribe and seeing in the meeting as strength. This is what we observe among most of the poets of Andalusia.